Desenvolvimento de judocas brasileiros talentosos - Massa, M. (2006)
The Brazilian Judo is a sport modality that has an Olympic tradition. However, about Brazilian judokas development process, it is unknown the facts that contribute for the talent development in this modality. The main purpose of the present study was to analyze the Brazilian Olympic Judokas development process and the relation between Brazilian Olympic Judokas and the patterns of talent reported in the literature. In order to do the research, it was used a sample of six judokas from the Brazilian Olympic Team of Atenas, 2004. The study was built through a qualitative inquiry, that used as instrument a interview composed by twelve open questions, elaborated to explore the context of the judo talent development. In order to analyze the results acquired, it was used the "Discurso do Sujeito Coletivo". The speeches showed that the judokas development trajectory didn't reach the development models described in the literature, especially because of the lack of national sport development programs. Although, concerning the aspects related to family support, the pleasure of practice and the judokas determination, the present study corroborates with the literature, revealing the importance that psychosocial facts exerted in the development of Brazilian talented judokas.